Deconstructing Technostress: A Configurational Approach to Explaining Job Burnout and Job Performance - Pflügner, Katharina; Maier, Christian; Thatcher, Jason Bennett; Mattke, Jens; Weitzel, Tim (MIS Quarterly, 2024)
Understanding how technostressors lead to technostrain, such as high job burnout or low job performance, has become a core question in information systems (IS) research and practice. To unpack this relationship, we build on general systems theory to argue that the next step for technostress research is to go beyond examining the independent influences of technostressors and discuss how their interdependencies lead to technostrain. To illustrate our argument empirically, we use fuzzy-set qualitative comparative analysis (fsQCA) and identify four configurations of high- and low-intensity technostressors that lead to high job burnout and one that leads to low job performance. We show that three types of interdependencies among technostressors, i.e., complementarity, contingency, and substitution, form configurations that lead to technostrain. Within these configurations, high-intensity technostressors can mutually enhance their effects and low-intensity technostressors can buffer the impact of other high-intensity technostressors on technostrain. The results help to explain why organizational interventions that address independent technostressors may fail if they do not account for the interdependencies among technostressors. Our work provides evidence of the need to further develop theories that explain how and why interdependencies among technostressors lead to technostrain.